1998
DOI: 10.2307/1602678
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Managed Care on Mental Health Services for Children and Their Families

Abstract: For more than a decade, the philosophy of community-based systems of care has guided the delivery of mental health services for children and adolescents served by publicly funded agencies. This philosophy supports system attributes that include a broad array of services; interagency collaboration; treatment in the least-restrictive setting; individualized services; family involvement; and services responsive to the needs of diverse ethnic and racial populations. The notion of systems of care emerged in an era … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 4 publications
0
57
0
Order By: Relevance
“…The system-of-care approach to meeting the needs of children and adolescents with serious emotional disorders (Substance Abuse and Mental Health Services Administration [SAMHSA], 2004;Stroul & Friedman, 1986) endorses a solution that would bring together ontogenetic, micro-and mesosystemic players-including the youth with concerns, her or his family, and all of the service providers into one coordinated team-mental health, substance abuse, physical health, education, child welfare, vocational training, juvenile justice, other community services. Such teams have been implemented in a handful of rural communities across the country (e.g., Werrbach, Jenson, & Bubar, 2002).…”
Section: Schools Churches and Other Community-levelmentioning
confidence: 99%
“…The system-of-care approach to meeting the needs of children and adolescents with serious emotional disorders (Substance Abuse and Mental Health Services Administration [SAMHSA], 2004;Stroul & Friedman, 1986) endorses a solution that would bring together ontogenetic, micro-and mesosystemic players-including the youth with concerns, her or his family, and all of the service providers into one coordinated team-mental health, substance abuse, physical health, education, child welfare, vocational training, juvenile justice, other community services. Such teams have been implemented in a handful of rural communities across the country (e.g., Werrbach, Jenson, & Bubar, 2002).…”
Section: Schools Churches and Other Community-levelmentioning
confidence: 99%
“…13 Moreover, the fact that children are often involved with multiple service systems increases the likelihood for cost-shifting within managed care. 8,14 In a recent review, Hutchinson and Foster 8 identified only two studies between 1995 and 2001 that examined the effects of Medicaid managed care programs on quality of care for children; both evaluated the effects of Massachusetts_ behavioral health program on readmission rates 6,15 Callahan and colleagues 15 found that 30-day readmission rates for children and adolescents increased from 7.5% to 10.1%. Dickey et al 6 examined patterns of posthospitalization readmissions and outpatient follow-up within 30 days of discharge and found that continuity of care increased slightly for Aid to Families with Dependent Children (AFDC) Medicaid beneficiaries but decreased for disabled children; specifically, readmission rates increased and outpatient follow-up decreased for disabled children.…”
Section: Introductionmentioning
confidence: 99%
“…Systems of care look at the entire community of service planning and delivery available to the child and family, and organize community services as appropriate to support the child and family through all stages of need, of personal development, and of treatment with a goal of full participation in every phase of treatment planning (Stroul and Blau 2008;Rivera and Kutash 1994;Stroul and Friedman 1986 The continued emphasis on partnerships between families, youth, and private and public providers moves PAR from a theoretical model to practical application; hence, our question on how PAR is viewed within that community.…”
Section: Par In the Context Of System Of Carementioning
confidence: 99%